Resource Federalism and Conflict: An Analysis of Federal and Provincial Government Relations in Nepal - Kuikel, Asmit (Prashasan: The Nepalese Journal of Public Administration, 2025)
This paper examines the relationship between federal and provincial governments in Nepal in the context of resource distribution, conflict, and potential interventions for resolution—focusing on natural, human, and financial resources. A qualitative research methodology was employed, using data collected from literature reviews, interviews, key informant interviews, and focus group discussions. The study explores resource distribution with an emphasis on constitutional provisions and current practices. It highlights the tensions between the two levels of government concerning the utilization and jurisdiction over natural resources. Furthermore, it addresses conflicts related to human resource management and mobilization, including the roles of provincial police, provincial civil servants, and the authority for appointing provincial secretaries and chief administrative officers at the local level. In addition, the paper discusses financial conflicts involving federal grants, budgeting, and the broader mechanisms of intergovernmental fiscal transfers. It also explores the roles of the National Natural Resource and Fiscal Commission and the Interstate Council in resolving conflicts related to resource allocation and mobilization.